Long-term incidence of infective endocarditis according to the type of cardiac implantable electronic device: a nationwide comparison with moderate- and high-risk patient groups - Amna Alhakak; Lauge Østergaard; Mohammed Bakir Ahmad Lafta; Michael Vinther; Berit Thornvig Philbert; Henning Bundgaard; Lars Køber; Emil Loldrup Fosbøl (Europace, 2026)
Structured Abstract Background and Aims According to ESC guidelines, patients with a cardiac implantable electronic device (CIED) are considered at moderate risk of infective endocarditis (IE), irrespective of CIED type. However, comparative data across CIED types and IE risk groups are limited. We examined IE rates according to CIED type compared with moderate- and high-risk groups. Methods Danish nationwide registries were used to identify patients with first-time CIED implantation and reference populations at moderate and high risk of IE (2000–2022), based on ESC guidelines. The high-risk group included patients with a left-sided prosthetic valve. Patients with prior IE or left-sided prosthetic valve were excluded from the CIED group. The primary outcome was incident IE within 10 years. Results The study included 84,171 CIED recipients, 127,966 moderate-risk patients, and 23,505 high-risk patients. Pacemakers were the most common CIED type (74.9%), followed by ICD (16.6%), CRT-D (4.6%), and CRT-P (3.9%). Pacemaker recipients were the oldest (median 78.2 years) and most frail. The 10-year cumulative incidence of IE was lowest in pacemaker recipients (1.0% [95% CI:0.9-1.1]) and highest in CRT-D recipients (2.2% [95% CI:1.7-2.9]). In adjusted analyses, all CIED types were associated with higher IE rates than the moderate-risk group but lower than the high-risk group. Conclusion In this nationwide cohort, IE risk differed across CIED types, highest in CRT-D and lowest in pacemaker recipients. All CIED types were associated with higher risk than moderate-risk patients but lower risk than high-risk patients, supporting ESC classification. CRT-D recipients may warrant further evaluation of preventive strategies.